Soil CO2 venting as one of the mechanisms for tolerance of Zn deficiency by rice in flooded soils - Affholder, Marie-Cecile; Weiss, Dominik J.; Wissuwa, Matthias; Johnson-Beebout, Sarah E.; Kirk, Guy J.D. (Wiley, 2017)
We sought to explain rice (Oryza sativa) genotype differences in tolerance of zinc (Zn) deficiency in flooded paddy soils and the counter‐intuitive observation, made in earlier field experiments, that Zn uptake per plant increases with increasing planting density. We grew tolerant and intolerant genotypes in a Zn‐deficient flooded soil at high and low planting densities and found (a) plant Zn concentrations and growth increased with planting density and more so in the tolerant genotype, whereas the concentrations of other nutrients decreased, indicating a specific effect on Zn uptake; (b) the effects of planting density and genotype on Zn uptake could only be explained if the plants induced changes in the soil to make Zn more soluble; and (c) the genotype and planting density effects were both associated with decreases in dissolved CO2 in the rhizosphere soil solution and resulting increases in pH. We suggest that the increases in pH caused solubilization of soil Zn by dissolution of alkali‐soluble, Zn‐complexing organic ligands from soil organic matter. We conclude that differences in venting of soil CO2 through root aerenchyma were responsible for the genotype and planting density effects.